Integrated System Health Management by Using the Index Based Reasoning (IBR) and Self Organizing Map (SOM) Combination - (:unkn) unknown (IEEE, 2009)
Integrated System Health Management (ISHM) will be an important component of the future launching vehicles and satellites. ISHM uses large number of sensors to evaluate the condition of the entire system. It is responsible to take the necessary corrective actions and to change the course of action if the health of the system will not allow successful completion of the mission. In this paper, Self Organizing Map (SOM) is integrated into the previously introduced Index Based Reasoner (IBR). The Simulink model of the proposed IBR-SOM approach is demonstrated and performance of the system is evaluated on the experimental data.
Keywords: IBR; SOM; Neural Network; System Health Management; FUSION